Vej og gravplads – Et exempel fra Møllegårdsmarken på Fyn - Thrane, Henrik (Kuml, 2013)
Road and cemetery – an example from the Iron Age at Møllegårdsmarken near Gudme on eastern Funen The cemetery at Møllegårdsmarken (fig. 1) is Denmark’s largest Iron Age burial ground, in use from late Pre-Roman to late Roman times. 1-4 During the recent attempt to excavate the cemetery completely, traces of paved roads and mortuary houses were observed, 5-6 and the ford across the river valley south of the cemetery was sampled in 1998. Close relations between roads and burials are well known from the Neolithic to medieval times. The roads at Møllegårdsmarken could only be observed where they had been well covered, but the fragments show that the cemetery functioned as a sort of crossroads (fig. 2). The road metalling simply comprised up to 10 cm thick layers of small stones which showed grooves made by the wheels of vehicles that used the road (fig. 3). The wheel span corresponds to the vehicle types known from the time. Parallels are rare. Potsherds from the roads have been 14C dated and a dendrochronological date of AD 1210 has been obtained for a post placed in the middle of one of the sunken roads leading to the ford (fig. 5), indicating a terminus ante quem for the use of this particular road. A further terminus ante quem is provided by fill from a pyre which overlay road ADF; the fill could be dated to the Migration period (fig. 6). In order to see where the road led, two trenches were dug in the Tange river valley (figs. 7-9). Trench ANU was found to contain stone pavement ANV (fig. 7), and stakes at the edges of this have been dated to AD 640, with alder roots giving dates of AD 440-430. Trench ANT revealed three separate stone pavements in hollows where the road had branched out in order to ascend the southern slope of the river valley (figs. 8-9). East of trench AOF, stake AOK gave a date of AD 435. No finds were encountered, so the 14C dates provide the only available dating evidence. Small constructions comprised of four or more posts, some containing cremation graves, are interpreted as mortuary houses. Several have been identified – LQ, ZP containing four urns, 2213-14, AGA containing urn 2212 50 and AHG containing ashes AKV. Their position is marginal to the cemetery and a close relationship with the roads seems quite clear (figs. 2 and 10). The cemetery appears to have functioned as a sort of crossroads. While the wheel grooves in the road surfaces indicate heavy loads, the roads can also be seen as elements in a processional route connecting important stages of a ritual, whose character remains unknown (fig. 11). The sacral place names in the vicinity indicate the special importance of the Gudme region at least during the late Roman and Migration periods. A German version of this paper has been published in the Steuer Festschrift (Thrane 2009). Henrik Thrane Forhistorisk Arkæologi Institut for Kultur og Samfund Aarhus Universitet